Microenvironment‐Responsive Prodrug‐Induced Pyroptosis Boosts Cancer Immunotherapy - Xiao, Yao; Zhang, Tian; Ma, Xianbin; Yang, Qi‐Chao; Yang, Lei‐Lei; Yang, Shao‐Chen; Liang, Mengyun; Xu, Zhigang; Sun, Zhi‐Jun (Advanced science, 2021)
The absence of tumor antigens leads to a low response rate, which represents a major challenge in immune checkpoint blockade (ICB) therapy. Pyroptosis, which releases tumor antigens and damage‐associated molecular patterns (DAMPs) that induce antitumor immunity and boost ICB efficiency, potentially leads to injury when occurring in normal tissues. Therefore, a strategy and highly efficient agent to induce tumor‐specific pyroptosis but reduce pyroptosis in normal tissues is urgently required. Here, a smart tumor microenvironmental reactive oxygen species (ROS)/glutathione (GSH) dual‐responsive nano‐prodrug (denoted as MCPP) with high paclitaxel (PTX) and photosensitizer purpurin 18 (P18) loading is rationally designed. The ROS/GSH dual‐responsive system facilitates the nano‐prodrug response to high ROS/GSH in the tumor microenvironment and achieves optimal drug release in tumors. ROS generated by P18 after laser irradiation achieves controlled release and induces tumor cell pyroptosis with PTX by chemo‐photodynamic therapy. Pyroptotic tumor cells release DAMPs, thus initiating adaptive immunity, boosting ICB efficiency, achieving tumor regression, generating immunological memory, and preventing tumor recurrence. Mechanistically, chemo‐photodynamic therapy and control‐release PTX synergistically induce gasdermin E (GSDME)‐related pyroptosis. It is speculated that inspired chemo‐photodynamic therapy using the presented nano‐prodrug strategy can be a smart strategy to trigger pyroptosis and augment ICB efficiency. A smart tumor microenvironmental reactive oxygen species/glutathione dual‐responsive nano‐prodrug (denoted as MCPP) with high paclitaxel and photosensitizer purpurin 18 loading is designed. Chemo‐photodynamic therapy using the presented nano‐prodrug strategy can be a smart strategy to trigger pyroptosis and augment the efficiency of immune checkpoint blockade therapy.